INNOVATION OF ALTERNATIVE YOGURT PRODUCTS FROM NUTS : SYSTEMATIC REVIEW - Hartono, Angela Puteri; Purwanto, Divina Elaine; Zulaikha, Siti; Rizkaprilisa, Windy; Paramastuti, Ratih; Hapsari, Martina Widhi (Fakultas Sains dan Teknologi, Universitas Nasional Karangturi, 2024)
One result of probiotic fermentation is yogurt, usually made from cow's milk. The latest innovation makes it possible to make yogurt from plant ingredients. Vegan yogurt has development potential due to its functional content and high nutritional value. This yogurt is made from nuts, rich in fiber, lactose-free, and casein-free. Soybeans, green beans, kidney beans, almonds, peanuts, and Arbilan nuts as plant protein sources can be used as an alternative to making plant-based yogurt. The results show the potential of nut yogurt as a functional food product that can support health, emphasizing its benefits in reducing the risk of hypertension. This article provides an in-depth overview of the development and opportunities for developing nut-based yogurt products as a healthy alternative.